Sevoflurane mitigates shedding of hyaluronan from the coronary endothelium, also during ischemia/reperfusion: an ex vivo animal study - Chen, Congcong (Hypoxia (Auckl), 2016)
Glycosaminoglycan hyaluronan (HA), a major constituent of the endothelial glycocalyx, helps to maintain vascular integrity. Preconditioning the heart with volatile anesthetic agents protects against ischemia/reperfusion injury. We investigated a possible protective effect of sevoflurane on the glycocalyx, especially on HA. The effect of pre-ischemic treatment with sevoflurane (15 minutes at 2% vol/vol gas) on shedding of HA was evaluated in 28 isolated, beating guinea pig hearts, subjected to warm ischemia (20 minutes at 37°C) followed by reperfusion (40 minutes), half with and half without preconditioning by sevoflurane. HA concentration was measured in the coronary effluent. Over the last 20 minutes of reperfusion hydroxyethyl starch (1 g%) was continuously infused and the epicardial transudate collected over the last 5 minutes for measuring the colloid extravasation. Additional hearts were fixed by perfusion after the end of reperfusion for immunohistology and electron microscopy. Sevoflurane did not significantly affect post-ischemic oxidative stress, but strongly inhibited shedding of HA during the whole period, surprisingly even prior to ischemia. Immunohistology demonstrated that heparan sulfates and SDC1 of the glycocalyx were also preserved by sevoflurane. Electron microscopy revealed shedding of glycocalyx caused by ischemia and a mostly intact glycocalyx in hearts exposed to sevoflurane. Coronary vascular permeability of the colloid hydroxyethyl starch was significantly decreased by sevoflurane vs the control. We conclude that application of sevoflurane preserves the coronary endothelial glycocalyx, especially HA, sustaining the vascular barrier against ischemic damage. This may explain beneficial effects associated with clinical use of volatile anesthetics against ischemia/reperfusion injury.